Water-sealable decorative adhesive film
The water-sealable decorative adhesive film with a structured surface and crosslinked binder addresses water ingress issues by using a water-absorbing resin to maintain adhesion and prevent peeling, suitable for various surfaces and environments.
Patent Information
- Application Number
- JP2020119354
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-07-10
AI Technical Summary
Existing decorative adhesive films face issues with water ingress through channels formed at the interface with adherends, leading to reduced adhesive strength and peeling, especially in environments where they come into contact with water, and methods to prevent this are labor-intensive and costly.
A water-sealable decorative adhesive film with a structured surface and a crosslinked adhesive binder containing a water-absorbing resin, which forms channels for air passage while preventing water ingress, using a crosslinked adhesive binder and water-absorbing resin to maintain adhesion and prevent water penetration.
The film effectively reduces water ingress at the interface, maintaining adhesive strength and preventing peeling, even in wet environments, while ensuring good adhesion to both flat and uneven surfaces.
Smart Images

Figure 0007609578000004 
Figure 0007609578000005 
Figure 0007609578000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to decorative adhesive films. [Background technology]
[0002] In recent years, various adhesive films have been developed and are being used in a wide range of fields, such as interior and exterior applications.
[0003] Patent Document 1 (JP 09-157606 A) describes an adhesive film that can be used outdoors, comprising I) a support and II) an adhesive layer formed on the support and containing adhesive elastic microspheres and an adhesive polymer, wherein a) the adhesive layer has convex adhesive parts containing an adhesive polymer and clusters formed by gathering at least two elastic microspheres, and b) when the adhesive film is attached to the surface of a flat glass plate at a pressure of 1 kg / cm and measured, the area contact rate between the adhesive layer and the plate surface is 20 to 90%.
[0004] Patent Document 2 (JP 2018-178080 A) describes an adhesive film that can be used on the walls of buildings, etc., which comprises a rigid substrate having a thickness of 80 micrometers or more and 500 micrometers or less, and a first pressure-sensitive adhesive layer arranged on one side of the rigid substrate or above it, the first pressure-sensitive adhesive layer comprising elastic resin microspheres having a volume average particle diameter of 110 micrometers or more and an adhesive binder, and the first pressure-sensitive adhesive layer has an uneven surface due to the presence of the microspheres. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 09-157606 [Patent Document 2] JP 2018-178080 A Summary of the Invention [Problem to be solved by the invention]
[0006] When an adhesive film is used for decorative purposes, in order to prevent poor appearance due to air pockets that may occur at the interface between the adherend and the adhesive film, an uneven layer such as those described in Patent Documents 1 and 2 may be formed on the adhesive layer of the adhesive film so as to form a channel (passageway) communicating with the outside air at the interface.
[0007] When an adhesive film capable of forming such channels is used in an environment where it may come into contact with water, water may penetrate into the interface between the adherend and the adhesive film through the channels due to capillary action or the like, which may result in a decrease in adhesive strength and problems such as peeling. In order to prevent such water penetration, it is possible to edge seal the ends of the film or reinforce them with other films. However, such methods require labor and may lead to increased costs.
[0008] When the adherend is a porous body such as concrete, water that has soaked into the adherend may seep out to the interface between the adherend and the adhesive film, and in such cases it has been difficult to prevent water penetration.
[0009] The present disclosure provides a water-sealable decorative adhesive film that can reduce or prevent the infiltration of water into the interface between the adhesive layer and the adherend, even in an environment where contact with water is possible. [Means for solving the problem]
[0010] According to one embodiment of the present disclosure, a water-sealable decorative adhesive film is provided, comprising a substrate and an adhesive layer having a structured surface disposed on the substrate, the adhesive layer comprising a tacky binder having a crosslinked structure derived from a crosslinking agent, and a water-absorbing resin.
[0011] According to another embodiment of the present disclosure, there is provided a structure in which the above-mentioned water-sealable decorative adhesive film is disposed on an adherend via an adhesive layer. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a water-sealing decorative adhesive film that can reduce or prevent the penetration of water into the interface between the adhesive layer and the adherend, even in an environment where contact with water may occur.
[0013] The above description should not be considered as a disclosure of all embodiments of the present invention and all advantages associated with the present invention. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a cross-sectional view of a water-sealable decorative adhesive film according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view of a water sealable decorative adhesive film according to another embodiment of the present disclosure. [Diagram 3] FIG. 2 is a cross-sectional view of a water sealable decorative adhesive film according to another embodiment of the present disclosure. [Figure 4] 1 is a schematic diagram showing a state in which water infiltration is prevented in a water-sealable decorative adhesive film according to one embodiment of the present disclosure applied to an adherend. [Diagram 5] (a) is a photograph of the sample of Comparative Example 1 after the water sealing test, (b) is a photograph of the sample of Example 3 after the water sealing test, (c) is a photograph of the sample of Example 4 after the water sealing test, and (d) is a photograph of the sample of Example 5 after the water sealing test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, for the purpose of illustrating representative embodiments of the present invention, the present invention will be described in more detail with reference to the drawings as necessary, but the present invention is not limited to these embodiments. Regarding the reference numbers of the drawings, elements with similar numbers in different drawings indicate similar or corresponding elements.
[0016] In the present disclosure, the term "film" also encompasses an article called a "sheet."
[0017] In the present disclosure, for example, "on" in "the decorative layer is disposed on the substrate" means that the decorative layer is disposed directly on the upper side of the substrate, or that the decorative layer is disposed indirectly on the upper side of the substrate via another layer.
[0018] In the present disclosure, for example, "under" in "the adhesive layer is disposed under the substrate" intends that the adhesive layer is disposed directly under the substrate, or that the adhesive layer is disposed indirectly under the substrate via another layer.
[0019] In the present disclosure, the term "structured surface" refers to an uneven surface that can form channels (passages) communicating with the outside air at the interface between the adhesive film and an adherend when the adhesive film is applied to the adherend.
[0020] In the present disclosure, the term "water-sealing property" refers to the ability to reduce or prevent the infiltration of water into the interface between the adhesive film and the adherend.
[0021] In this disclosure, the term "approximately" means including variations that occur due to manufacturing errors and the like, and is intended to allow for a variation of about ±20%.
[0022] In the present disclosure, "transparent" refers to an average transmittance of about 80% or more, preferably about 85% or more, or about 90% or more, in the visible light region (wavelength 400 nm to 700 nm) measured in accordance with JIS K 7375. There is no particular limit to the upper limit of the average transmittance, but it can be, for example, less than about 100%, about 99% or less, or about 98% or less.
[0023] In the present disclosure, the term "semi-transparent" refers to an average transmittance in the visible light region (wavelength 400 nm to 700 nm) measured in accordance with JIS K 7375 of less than about 80%, desirably about 75% or less, and is intended to not completely conceal the base.
[0024] In this disclosure, "(meth)acrylic" means acrylic or methacrylic, and "(meth)acrylate" means acrylate or methacrylate.
[0025] The water-sealable decorative adhesive film of the present disclosure will be described below with reference to the drawings as necessary.
[0026] The water-sealable decorative adhesive film 100 in FIG.
[0027] Hereinafter, for the purpose of illustrating representative embodiments of the present disclosure, details of each component will be described with some reference numerals omitted.
[0028] The water-sealable decorative adhesive film (sometimes simply referred to as "adhesive film") of the present disclosure includes a substrate. Such a substrate can be used as a support for an adhesive layer or any other layer (e.g., a decorative layer). The substrate may have a receptor layer on its surface, or the substrate itself may have receptor properties. By using a substrate having a receptor layer or receptor properties, a decorative layer such as a graphic image can be formed directly on the substrate by using inkjet printing or the like.
[0029] For example, an adhesive layer may be applied to one side of the substrate, and an optional layer such as a decorative layer may be applied to the other side, or an optional layer such as a decorative layer may be applied to one side of the substrate, and an adhesive layer may be applied on the layer. When an adhesive film having the latter configuration is applied to an adherend via an adhesive layer, the substrate is configured to be disposed as the outermost layer, so that the substrate can exhibit the same function as a protective layer. The substrate may be subjected to a surface treatment such as embossing, corona treatment, plasma treatment, etc. for the purpose of decoration, etc.
[0030] Examples of materials for the substrate include polyvinyl chloride resins, polyurethane resins, polyolefin resins (e.g., polyethylene, polypropylene), polyester resins (e.g., polyethylene terephthalate, polyethylene naphthalate), polycarbonate resins, polyimide resins, polyamide resins, (meth)acrylic resins, and fluororesins (e.g., polytetrafluoroethylene, polyvinylidene fluoride). These may be used alone or in combination of two or more.
[0031] The thickness of the substrate is not particularly limited and can be appropriately selected depending on the use of the adhesive film, for example, about 50 micrometers or more, about 80 micrometers or more, about 100 micrometers or more, or about 150 micrometers or more. There is no particular limit to the upper limit of the thickness, but from the viewpoint of rigidity, manufacturing cost, etc., it can be, for example, about 500 micrometers or less, about 400 micrometers or less, about 300 micrometers or less, or about 200 micrometers or less. Here, the thickness of each layer constituting the adhesive film can be typically defined as the average value of the thickness of the target layer of the laminated structure, for example, at least five arbitrary points in the substrate, by measuring the thickness direction cross section of the laminated structure using a scanning electron microscope.
[0032] In some embodiments, a substrate exhibiting rigidity (sometimes referred to as a "rigid substrate") can be used. Such a substrate can, for example, prevent the deformation of the adhesive film caused by the swelling of the water-absorbing resin in the adhesive layer, or can resist the stress caused by the deformation of the microspheres contained in the adhesive layer when the adhesive film is applied, thereby preventing the deformation of the adhesive film, and as a result, contribute to maintaining the smooth appearance of the adhesive film. When the adherend has an uneven surface, the rigid substrate can suppress the adhesive film from excessively following the uneven surface during adhesion, and can prevent the protrusions of the uneven surface from penetrating the adhesive film. When the adhesive film is applied to a vertical surface, the rigid substrate can suppress the deformation of the adhesive film and prevent peeling due to its own weight.
[0033] In some embodiments, the yield modulus of the rigid substrate can be about 10 MPa or more, about 15 MPa or more, or about 20 MPa or more, and about 300 MPa or less, about 250 MPa or less, or about 200 MPa or less. When the yield modulus of the rigid substrate is in the above range, in combination with the thickness of the substrate, the smoothness of the appearance of the adhesive film can be well maintained during adhesion. The yield modulus is defined as the modulus at the yield point when the rigid substrate is cut into a rectangle having a width of 15 mm and a length of 100 mm to prepare a test piece, and the elongation property of the test piece is measured in accordance with JIS K 7127 using a tensile tester under the conditions of 20°C, grip interval of 50 mm, and tensile speed of 300 mm / min.
[0034] In some embodiments, the product of the yield modulus and thickness of the rigid substrate is about 0.9×10 4 N / m or more, approximately 1.0×10 4 N / m or more, or about 1.5×10 4 N / m or more, and approximately 5×10 4 N / m or less, approximately 4×10 4 N / m or less, or about 3×10 4 N / m or less. The product of the yield modulus and thickness is proportional to the bending rigidity of the rigid substrate. By setting the product of the yield modulus and thickness of the rigid substrate within the above range, the rigid substrate can have sufficient bending rigidity to maintain the smoothness of the appearance of the adhesive film when adhered.
[0035] In some embodiments, the 2% tensile strength of the rigid substrate can be about 40 N / 25 mm or more, about 45 N / 25 mm or more, or about 50 N / 25 mm or more. By setting the 2% tensile strength of the rigid substrate within the above range, the smooth appearance of the adhesive film can be maintained during adhesion, and the adhesive film can be removed without breaking or destroying the adhesive film and causing the adhesive film to remain. The 2% tensile strength is defined as the tensile strength at 2% elongation when a test piece is prepared by cutting the rigid substrate into a rectangle with a width of 25 mm and a length of 100 mm, and measured using a tensile tester under the conditions of 20° C., grip interval of 50 mm, and tensile speed of 300 mm / min.
[0036] The substrate may be a stretched film or a non-stretched film. The substrate may be a stretched film, particularly a biaxially stretched film, which can advantageously increase the stiffness and tensile strength of the substrate.
[0037] The substrate is typically preferably transparent or translucent (e.g., milky white), but may be wholly or partially transparent, translucent, or opaque in the visible range to provide the desired appearance. The substrate may be colorless or may be wholly or partially colored.
[0038] The substrate may contain other optional components such as fillers, colorants such as pigments or dyes, ultraviolet absorbers, antioxidants, light stabilizers, flame retardants, antibacterial agents, and deodorants.
[0039] The water sealable decorative adhesive film of the present disclosure includes an adhesive layer having a structured surface.
[0040] The topography (surface shape or features) of the structured surface formed on the surface of the adhesive layer disposed on a substrate is not particularly limited, so long as a network of channels or similar structures through which air can pass laterally is formed at the interface between the adhesive layer and the adherend when the structured surface side of the adhesive layer is applied to the adherend.
[0041] The structured surface of the adhesive layer can be formed, for example, by (1) applying the adhesive composition onto a release liner having a textured surface, such as an embossed pattern, corresponding to the structured surface, (2) by compressing an adhesive layer applied to a release liner having a textured surface, such as an embossed pattern, corresponding to the structured surface, or (3) by applying an adhesive composition containing microspheres to a substrate.
[0042] The means for applying the adhesive composition to the release liner or substrate is not particularly limited, and may be, for example, a knife coater, gravicoater, roll coater, die coater, bar coater, etc. After the adhesive composition is applied, the solvent may be dried as necessary. Drying may be performed, for example, at a temperature of 60°C to 120°C for 10 seconds to 10 minutes.
[0043] An adhesive layer having a structured surface typically has a maximum thickness corresponding to the distance from the top of a protrusion in one convex region (e.g., a convex region around a microsphere indicated by reference numeral 107 in FIG. 1) to the surface of another layer adjacent to the adhesive layer (e.g., a substrate surface), and a minimum thickness corresponding to the distance from the bottom of a recess formed between the other convex region adjacent to the protrusion region to the surface of another layer adjacent to the adhesive layer (e.g., a substrate surface), as shown in FIG. 1 to FIG. 3. The difference between the maximum thickness and the minimum thickness of the adhesive layer is one of the indices showing the topography of the structured surface of the adhesive layer, and for example, such an indices may relate to the adhesion to a rough surface portion.
[0044] In some embodiments, the difference between the maximum thickness and the minimum thickness of the adhesive layer can be about 50 micrometers or more, about 70 micrometers or more, or about 90 micrometers or more, and about 400 micrometers or less, about 350 micrometers or less, or about 300 micrometers or less. By setting the difference between the maximum thickness and the minimum thickness of the adhesive layer within the above range, for example, the adhesive film can be well adhered to a rough surface portion having protrusions with a height of 1 to 2 mm. The maximum thickness and the minimum thickness of the adhesive layer can be defined as the average value of each thickness based on, for example, any of at least five convex regions in the adhesive layer, measured by using a scanning electron microscope in the thickness direction cross section of the adhesive film.
[0045] The 60 degree gloss of the structured surface of the adhesive layer is another index showing the topography of the structured surface of the adhesive layer, and for example, such an index is related to the adhesion to a rough surface. In some embodiments, the 60 degree gloss of the adhesive layer can be about 3 or more, about 4 or more, or about 5 or more, and can be about 60 or less, about 55 or less, or about 50 or less. By setting the 60 degree gloss of the adhesive layer in the above range, for example, the pressure-sensitive adhesive sheet can be adhered with high adhesive strength even to a rough surface portion having protrusions with a height of 1 to 2 mm. The 60 degree gloss is defined as a value measured in accordance with JIS Z8741.
[0046] The thickness of the adhesive layer having a structured surface corresponds to the maximum thickness described above.The thickness of the adhesive layer is not particularly limited, and can be, for example, about 30 micrometers or more, about 40 micrometers or more, about 50 micrometers or more, about 60 micrometers or more, about 70 micrometers or more, or about 80 micrometers or more, and can be about 220 micrometers or less, about 200 micrometers or less, or about 180 μm or less.
[0047] The adhesive layer of the present disclosure contains an adhesive binder having a crosslinked structure derived from a crosslinking agent, and a water-absorbent resin. In the field of decorative films, shrinkage of the film after being attached to an adherend may lead to a decrease in decorative performance. The adhesive binder constituting the adhesive layer of the present disclosure has a crosslinked structure derived from a crosslinking agent, so that such shrinkage of the film can be reduced or suppressed. On the other hand, an adhesive layer containing an adhesive binder having a crosslinked structure has better shape retention than an adhesive layer containing an adhesive binder without a crosslinked structure, so that even if the adhesive film is attached to the adherend by applying pressure using a roller or spatula, the channel at the interface tends to be maintained. While such a channel can, for example, allow gas such as water vapor that may be generated from the adherend to escape, it may cause peeling due to the infiltration of water. Since the adhesive layer of the present disclosure contains a water-absorbent resin, for example, when water comes into contact with the edge of the adhesive film applied to the adherend, or when water that has seeped out of a porous adherend comes into contact with the adhesive layer, the water-absorbent resin that has absorbed the water will swell, thereby reducing or preventing the infiltration of water through channels, etc.
[0048] The adhesive binder is not particularly limited as long as it has a crosslinked structure derived from a crosslinking agent, and known resins such as (meth)acrylic resins, polyurethanes, polyolefins, polyesters, rubber-based resins, silicone resins, and vinyl acetate resins can be used. These resins can be used alone or in combination of two or more. Among them, (meth)acrylic resins are preferred from the viewpoints of adhesiveness, water sealing properties, dispersibility of water-absorbent resins, and the like.
[0049] The crosslinked structure of the adhesive binder can be imparted, for example, by applying an adhesive composition containing an adhesive binder, a crosslinking agent, and a water-absorbing resin to a substrate, and then heating or irradiating the composition with ionizing radiation (e.g., X-rays, electron beams, ultraviolet rays, visible light, infrared rays).
[0050] The crosslinking agent is not particularly limited, and a known crosslinking agent, such as a thermal crosslinking agent or an ultraviolet crosslinking agent, can be used. By crosslinking the adhesive binder using a crosslinking agent, the cohesive force of the adhesive layer can be increased, and the reworkability and / or dimensional stability of the adhesive film can be improved. The crosslinked structure of the adhesive binder can also contribute to the swelling property of the water-absorbing resin contained in the adhesive layer, i.e., the adhesiveness and water penetration resistance of the adhesive layer. The more the water-absorbing resin absorbs water and becomes larger, the easier it is to prevent water penetration, but since water-absorbing resins generally do not exhibit adhesive performance, an increase in the volume of the water-absorbing resin may reduce the adhesiveness. In other words, adjustment of the crosslinked structure of the adhesive binder can contribute to adjustment of the swelling property of the water-absorbing resin, i.e., adjustment of the adhesiveness and water sealing property of the adhesive film.
[0051] As the thermal crosslinking agent, it is preferable to use a thermal crosslinking agent selected from the group consisting of epoxy crosslinking agents and bisamide crosslinking agents, for example, from the viewpoints of adhesion, dimensional stability, swelling property of water-absorbing resin, etc. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-1,3-benzenedi(methaneamine) (manufactured by Mitsubishi Gas Chemical Company, Inc.: TETRAD-X), E-AX, E-5XM, and N,N'-(cyclohexane-1,3-diylbismethylene)bis(diglycidylamine) (manufactured by Mitsubishi Gas Chemical Company, Inc.: TETRAD-C), and E-5C, both manufactured by Soken Chemical Company, Inc. Examples of bisamide crosslinking agents include 1,1'-(1,3-phenylenedicarbonyl)-bis(2-methylaziridine) (1,1'-isophthaloyl-bis(2-methylaziridine)), 1,4-bis(ethyleneiminocarbonylamino)benzene, 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane, and 1,8-bis(ethyleneiminocarbonylamino)octane.
[0052] The amount of the thermal crosslinking agent may be about 0.01 parts by mass or more, about 0.02 parts by mass or more, or about 0.05 parts by mass or more, and about 0.5 parts by mass or less, about 0.4 parts by mass or less, or about 0.3 parts by mass or less, per 100 parts by mass of the adhesive binder, from the standpoints of the reworkability of the adhesive layer, dimensional stability, swelling properties of the water-absorbing resin, etc.
[0053] Examples of the ultraviolet crosslinking agent include compounds having a hydrogen radical abstracting structure such as a benzophenone structure, a benzyl structure, an o-benzoylbenzoic acid ester structure, a thioxanthone structure, a 3-ketocoumarin structure, a 2-ethylanthraquinone structure, and a camphorquinone structure, from the viewpoints of adhesion, dimensional stability, swelling property of the water-absorbing resin, etc. In terms of transparency and reactivity, it is advantageous to use a compound having a benzophenone structure.
[0054] The ultraviolet crosslinking agent may be a (meth)acrylic polymer having a hydrogen radical abstracting structure selected from the group consisting of a benzophenone structure, a benzyl structure, an o-benzoylbenzoic acid ester structure, a thioxanthone structure, a 3-ketocoumarin structure, a 2-ethylanthraquinone structure, and a camphorquinone structure. By using a (meth)acrylic polymer having a hydrogen radical abstracting structure, the crosslinking reactivity can be increased while adjusting the viscosity of the adhesive composition. In one embodiment, the ultraviolet crosslinking agent is a benzophenone-modified (meth)acrylic polymer.
[0055] The amount of the ultraviolet crosslinking agent may be about 0.1 parts by mass or more, about 0.5 parts by mass or more, or about 1 part by mass or more, and about 20 parts by mass or less, about 10 parts by mass or less, or about 5 parts by mass or less, per 100 parts by mass of the adhesive binder, from the standpoints of the reworkability of the adhesive layer, dimensional stability, swelling properties of the water-absorbing resin, etc.
[0056] The water-absorbing resin is typically in the form of particles and may be present in a dispersed state in the adhesive binder.
[0057] The water-absorbing resin is not particularly limited, and known water-absorbing resins can be used. Examples of the resin material of the water-absorbing resin include sodium polyacrylate, acrylic acid-vinyl alcohol copolymer, sodium polyacrylate crosslinked body, starch-acrylic acid graft copolymer, isobutylene-maleic anhydride copolymer and its saponification product, polyaspartic acid, etc. Among them, sodium polyacrylate is most preferable because it has a water absorption capacity of 100 to 1000 times its own weight. The water-absorbing resin to be blended in the adhesive layer may be composed of a single resin material, or may be composed of two or more resin materials.
[0058] The water-absorbent resin typically has a particle form, and the average particle diameter thereof is preferably about 10 micrometers or more, about 30 micrometers or more, or about 50 micrometers or more, and about 500 micrometers or less, about 300 micrometers or less, or about 100 micrometers or less, from the viewpoints of dispersibility in the adhesive binder, water sealing property, etc. 50 The D value can be measured by a sieving method. 50 The value is given when 50% by volume of the particles are retained by a sieve having the corresponding mesh size.
[0059] The amount of the water-absorbing resin is, in terms of adhesiveness, water-sealing property, and the like, preferably about 1 part by mass or more, about 2 parts by mass or more, or about 3 parts by mass or more, and about 30 parts by mass or less, about 20 parts by mass or less, about 10 parts by mass or less, less than about 10 parts by mass, about 9 parts by mass or less, or about 8 parts by mass or less per 100 parts by mass of the adhesive binder (100% solid content) in terms of solid matter. The water-absorbing resin does not exhibit adhesiveness, but swells with absorption of water to exhibit water-sealing property. When the amount of the water-absorbing resin is within the above range, an adhesive layer with a better balance between adhesiveness and water-sealing property can be obtained.
[0060] In some embodiments, the structured surface of the adhesive layer of the present disclosure can be prepared using an adhesive composition that includes microspheres 107, as shown in FIG.
[0061] The microspheres are not particularly limited, but from the viewpoint of the formability of a structured surface, microspheres having a volume average particle diameter of about 110 micrometers or more are preferred, and from the viewpoint of adhesion to an adherend, elastic resin microspheres having a volume average particle diameter of about 110 micrometers or more are more preferred.
[0062] In the present disclosure, "elastic resin microspheres" are defined as spherical materials formed of resin, and usually exhibit rubber elasticity as a whole microsphere. When an adhesive film is adhered to an adherend, the elastic resin microspheres can be deformed, for example, by being crushed in the thickness direction of the adhesive film, so that the contact area of the adhesive layer with the adherend surface increases, and the adhesive film can be well adhered to the adherend surface. Since the volume average particle diameter of the elastic microspheres is relatively large, similar to the fact that a thick pressure-sensitive adhesive layer has excellent adhesive strength, even if the contact area with the adherend is relatively small, high adhesive strength can be obtained by utilizing the elasticity of the microspheres. Since the uneven surface formed by the microspheres has a relatively large height difference, for example, the contact area with the rough surface of the adherend can also be increased, thereby increasing the adhesive strength.
[0063] In one embodiment, the elastic resin microspheres are adhesive. The adhesive elastic resin microspheres can be used to increase the adhesive strength.
[0064] The volume average particle size of the microspheres is about 110 micrometers or more. In some embodiments, the volume average diameter of the microspheres is about 125 micrometers or more or about 130 micrometers or more, and about 500 micrometers or less or about 300 micrometers or less. An adhesive layer containing microspheres with a volume average particle size in the above range can conform well to the adherend surface and exhibit high adhesive strength. The volume average particle size of the microspheres can be measured using a laser diffraction particle size analyzer, for example, Beckman Coulter LS230.
[0065] The compressive modulus of the elastic resin microspheres is preferably about 1 kPa or more and about 100 kPa or less at 20°C. By setting the compressive modulus of the elastic resin microspheres within the above range, the microspheres or clusters of microspheres, which are masses of two or more microspheres, can be deformed to be advantageous for adhesion to rough surfaces. The compressive modulus of the microspheres is a value measured at 20°C when a sample is prepared by molding the microspheres into a predetermined shape, for example, a cylindrical shape, and the sample is measured using a viscoelasticity measuring device, for example, an RSAII viscoelasticity spectrometer manufactured by Rheometrics, at a frequency of 1 rad / sec, in a compression strain mode, in a measurement temperature range of -80°C to 150°C, and at a heating rate of 5.0°C / min.
[0066] The material of the microspheres is not particularly limited, and for example, metal materials, inorganic materials, and resin materials can be used, but resin materials are preferred from the viewpoint of exhibiting the elasticity of the microspheres. Such resin materials can include, for example, (meth)acrylic resins, silicone resins, polyurethanes, vinyl acetate resins, fluororesins, polyamides, polyvinyl chloride, polystyrene, phenolic resins, epoxy resins, styrene-butadiene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-isoprene-styrene block copolymers, nitrile rubber, chloroprene rubber, and natural rubber. (Meth)acrylic resins are advantageously used because they have high weather resistance and are easy to control the adhesion. The microspheres to be mixed in the adhesive layer may be composed of a single material, or may be composed of two or more materials.
[0067] The microspheres may contain a crosslinked resin or a non-crosslinked resin. In one embodiment, the microspheres contain a crosslinked resin. Microspheres containing a crosslinked resin have excellent shape retention and durability, and therefore can be repeatedly attached and detached from the adhesive film.
[0068] The microspheres may comprise solid particles, hollow particles having one or more voids therein, or a mixture thereof, hi one embodiment, the microspheres are solid particles.
[0069] Microspheres made of a resin material can be produced by known polymerization methods such as suspension polymerization, emulsion polymerization, seed polymerization, etc. For example, microspheres containing a (meth)acrylic resin can be produced by suspension polymerization according to the following procedure.
[0070] Deionized water, monomer mixture, radical polymerization initiator, and optional additives are placed in a reactor equipped with a mechanical stirrer, the reactor is purged with an inert gas such as nitrogen gas, and the (meth)acrylic monomer is polymerized by heating to a predetermined temperature while stirring. The stirring speed is usually 10 to 700 rpm, the reaction temperature is usually 30 to 120°C, and the reaction time is usually several hours to several tens of hours.
[0071] The monomer mixture generally contains an alkyl (meth)acrylate (e.g., ethyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, etc.) and a carboxylic acid having an ethylenically unsaturated bond (e.g., (meth)acrylic acid, itaconic acid, maleic acid, etc.). The alkyl (meth)acrylate and the carboxylic acid having an ethylenically unsaturated bond may each be one type, or two or more types may be combined. The carboxylic acid having an ethylenically unsaturated bond is generally used in an amount of about 1 part by mass or more and about 10 parts by mass or less per 100 parts by mass of the alkyl (meth)acrylate. A polyfunctional monomer such as 1,4-butanediol diacrylate or divinylbenzene may be added to the mixture as a crosslinking agent to crosslink the (meth)acrylic resin. The amount of the crosslinking agent used is generally about 0.01 parts by weight or more, or about 0.02 parts by weight or more, and about 0.5 parts by weight or less, or about 0.1 parts by weight or less, based on 100 parts by weight of the monomer mixture. The microspheres obtained by polymerization may be separated by filtration, or may be used in the form of an aqueous dispersion containing the microspheres after completion of the reaction.
[0072] The glass transition temperature (Tg) of the resin contained in the microspheres is generally lower than room temperature, for example, about −90° C. or higher, about −70° C. or higher, or about −50° C. or higher, about 0° C. or lower, about −10° C. or lower, or about −20° C. The glass transition temperature can be adjusted by the types and compounding ratios of the monomers contained in the monomer mixture.
[0073] In one embodiment, the microspheres are contained in the adhesive layer in an amount of about 5 parts by weight or more, about 10 parts by weight or more, or about 15 parts by weight or more, and about 200 parts by weight or less, about 180 parts by weight or less, or about 160 parts by weight or less, per 100 parts by weight of the adhesive binder. By setting the content of the microspheres in the above range, it is possible to form an uneven structured surface on the adhesive layer that exhibits good adhesion even to rough surfaces.
[0074] In one embodiment, the mass ratio of the adhesive binder to the microspheres in the adhesive layer is from 40: 60 to 90: 10. By setting the mass ratio of the adhesive binder to the microspheres in the above range, it is possible to form an uneven structured surface on the adhesive layer that exhibits good adhesion even to rough surfaces.
[0075] The structured surface of the adhesive layer containing microspheres may be formed by one microsphere 107 as shown in FIG. 1, or may be formed by a mass of two or more microspheres aggregated together (sometimes referred to as a "microsphere cluster"). A microsphere cluster is an aggregate of microspheres that forms irregularly shaped and irregularly arranged protrusions in the adhesive layer. A cluster may include a plurality of microspheres aligned in the planar direction of the adhesive film, a plurality of microspheres stacked in the thickness direction of the adhesive sheet, or a combination of these. An island-like structure formed by the cluster may include an adhesive binder. A relatively flat sea portion of the adhesive layer that does not include clusters is present around the island-like structure.
[0076] When the microspheres are elastic resin microspheres, the microspheres in the clusters are deformed by pressure during application of the adhesive film to the adherend, and the adhesive protrusions are deformed into a shape suitable for adhering to the adherend surface. The degree of deformation can be controlled by the thickness and coating weight of the adhesive layer, the compressive elastic modulus of the microspheres, the compounding ratio of the microspheres and the adhesive binder, etc.
[0077] In one embodiment, the cluster contains 2 or more, about 5 or more, or about 10 or more, and about 200 or less, about 150 or less, or about 100 or less microspheres. By having the number of microspheres contained in the cluster within the above range, it is possible to improve the conformability to the adherend surface while suppressing the in-plane variation in adhesiveness. It is desirable that the number of clusters containing the above number of microspheres out of the total number of clusters is 80% or more. The formation of the microsphere clusters in the adhesive layer, their shape, size, etc. can be confirmed using reflected light from an optical microscope, usually at a magnification of 10 to 100 times.
[0078] By adjusting the viscosity of the adhesive composition and / or the wettability of the surface of a substrate or the like to which the adhesive composition is applied, it is possible to promote the formation of microsphere clusters and control the shape, arrangement, and size of the clusters. In some embodiments, the microspheres are dispersed in a composition containing a solvent and an adhesive binder, and when the solvent dries, the microspheres are dragged by the adhesive binder component dissolved in the solvent and move, and then aggregate to form clusters.
[0079] It is advantageous for promoting cluster formation to have a viscosity of the adhesive composition of about 100 mPa·s or more, or about 150 mPa·s or more, and about 6,000 mPa·s or less, or about 5,000 mPa·s or less.
[0080] The wettability of the surface of a substrate or the like to which the adhesive composition is applied can be controlled by surface treatments such as corona discharge treatment, plasma treatment, primer treatment, acid or alkali treatment, or by the type and amount of additives contained in the substrate, so that clusters are formed while preventing uneven application of the composition.
[0081] The surface of the adhesive layer having a structured surface prepared using microspheres may be protected by a release liner. The material and thickness of the release liner may be the same as that of the release liner having an embossed pattern described below.
[0082] In some embodiments, the structured surface of the adhesive layer of the present disclosure can be prepared using a release liner 309 having an indented surface, such as an embossed pattern, corresponding to the structured surface, as shown in FIG.
[0083] For example, an adhesive composition can be applied to the uneven surface of a release liner, and then dried and / or crosslinked as necessary to transfer the uneven pattern to the adhesive layer. By applying the adhesive layer of the release liner having the obtained adhesive layer to a substrate, an adhesive film 300 can be obtained in which a release liner 309 having an uneven surface corresponding to the structured surface is disposed on an adhesive layer 305 via the uneven surface, as shown in FIG. 3.
[0084] Alternatively, an adhesive composition may be applied onto a smooth first release liner, and optionally dried and / or crosslinked to form an adhesive layer, and then the adhesive layer may be applied to a second release liner having an uneven surface such as an embossed pattern corresponding to the structured surface, and optionally dried and / or crosslinked, and then pressed to transfer the uneven pattern to the adhesive layer. After removing the first release liner, the adhesive layer may be applied to a substrate to obtain an adhesive film 300 in which a release liner 309 having an uneven surface corresponding to the structured surface is disposed on an adhesive layer 305 via the uneven surface, as shown in FIG. 3.
[0085] The release liner is not particularly limited, and examples thereof include those prepared from paper (e.g., kraft paper), polymer materials (e.g., polyolefins such as polyethylene or polypropylene, polyesters such as ethylene vinyl acetate, polyurethane, and polyethylene terephthalate), etc. The release liner may have a layer of a release agent, such as a silicone-containing material or a fluorocarbon-containing material, applied thereto, as necessary.
[0086] The thickness of the release liner can be, for example, about 5 micrometers or more, about 15 micrometers or more, or about 25 micrometers or more, and can be about 300 micrometers or less, about 200 micrometers or less, or about 150 micrometers or less. The thickness of the release liner, i.e., the distance from the top to the bottom, can be defined as the average value calculated by measuring the thickness of any part of the release liner at least five times using a high-precision Digimatic Micrometer (MDH-25MB, manufactured by Mitutoyo Corporation) after removing the release liner from the adhesive layer.
[0087] The adhesive composition for forming the adhesive layer may contain other components in addition to the adhesive binder, crosslinking agent, and water-absorbing resin. Examples of the other components include fillers other than the above-mentioned microspheres, pigments, dyes, antioxidants, heat stabilizers, light stabilizers, UV absorbers, flame retardants, antibacterial agents, deodorants, tackifiers, other resins, etc. The other components may be used alone or in combination of two or more.
[0088] The adhesive composition may or may not contain a solvent. The solvent is not particularly limited, but from the viewpoint of the swelling resistance of the water-absorbing resin contained in the adhesive composition, an organic solvent is preferable. Examples of the organic solvent include methanol, ethanol, hexane, toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, butyl acetate, and the like, or a mixture thereof. In the case of an adhesive composition that does not contain a water-absorbing resin, which is used in the preparation of the first adhesive layer described below, water, an organic solvent, or a mixture thereof, can be used as the solvent. Examples of the aqueous solvent include a mixture of an alkylene glycol monoalkyl ether ester such as 3-methyl-3-methoxybutyl acetate and water.
[0089] In some embodiments, the adhesive layer may be a laminated structure including a first adhesive layer located on the substrate side and a second adhesive layer located on the outermost surface. For example, the first adhesive layer may include an adhesive binder having a crosslinked structure derived from a crosslinking agent and may optionally include microspheres and / or a water-absorbent resin, and the second adhesive layer may include an adhesive binder having a crosslinked structure derived from a crosslinking agent and a water-absorbent resin.
[0090] Such a laminated adhesive layer is advantageous when an adhesive layer 205 containing microspheres 207 is used, as shown in FIG. 2. When an adhesive layer containing microspheres is formed using an adhesive composition, the adhesive composition near the tops of the microspheres tends to flow toward the recesses (valleys). As a result, the layer containing the adhesive binder formed near the tops of the microspheres tends to become thinner like a skin compared to other parts, and performance such as adhesion may decrease. On the other hand, in the case of a laminated structure, a second adhesive layer can be laminated near the thin tops like a skin to form a thick film, thereby improving wettability, adhesion, etc. to the adherend.
[0091] The second adhesive layer containing the water-absorbing resin may be applied to the entire surface of the first adhesive layer, or may be applied partially to the first adhesive layer. For example, the second adhesive layer may be applied partially to the first adhesive layer located around the edge of the adhesive film, or may be applied to the recesses of the uneven structured surface as shown in Fig. 1, that is, the portions that can form channels through which air can pass laterally at the interface between the adhesive layer and the adherend when the structured surface side of the adhesive layer is applied to the adherend.
[0092] In some embodiments, the water-sealable decorative adhesive film of the present disclosure may further include additional layers as optional components, such as a protective layer, a decorative layer, a glittering layer, and a bonding layer (sometimes called a "primer layer" or a "third adhesive layer") that bonds the constituent layers together. These additional layers may be used alone or in combination of two or more kinds.
[0093] In some embodiments, a protective layer can be disposed on the outermost surface of the adhesive film opposite the adhesive layer. The protective layer may have a function of protecting other layers, such as a decorative layer, constituting the adhesive film from external punctures, impacts, etc.
[0094] The protective layer may be a multi-layer laminate, for example a multi-layer extrusion laminate. The protective layer may have a receptor layer on its surface, or the protective layer itself may have receptor properties. By using a protective layer having a receptor layer or receptor properties, a decorative layer such as a graphic image can be directly formed on the protective layer by inkjet printing or the like. The protective layer may have a substantially smooth surface, or may have an uneven shape such as a matte pattern or an embossed pattern on the surface. The protective layer may have a surface treatment such as a corona treatment or a plasma treatment applied to its surface.
[0095] As the material of the protective layer, various resins can be used, for example, (meth)acrylic resins including polymethyl methacrylate (PMMA), polyurethane, ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), fluororesins such as methyl methacrylate-vinylidene fluoride copolymer, silicone copolymers, polyvinyl chloride, polycarbonate, acrylonitrile-butadiene-styrene copolymer (ABS), polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), copolymers such as ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, and ethylene-vinyl acetate copolymer, or mixtures thereof. From the viewpoints of transparency, strength, impact resistance, etc., (meth)acrylic resins, polyurethane, fluororesins, polyvinyl chloride, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, and polycarbonate can be advantageously used as the material of the protective layer. Furthermore, from the viewpoint of weather resistance, (meth)acrylic resins are advantageous.
[0096] The protective layer may contain, as necessary, benzotriazole, an ultraviolet absorber such as Tinuvin™ 400 (manufactured by BASF), a hindered amine light stabilizer (HALS) such as Tinuvin™ 292 (manufactured by BASF), etc. By using an ultraviolet absorber, a hindered amine light stabilizer, etc., it is possible to effectively prevent deterioration of a layer located below the protective layer, for example, discoloration, fading, deterioration, etc. of a decorative layer. The protective layer may contain a hard coat material, a gloss imparting agent, etc., and may have an additional hard coat layer.
[0097] The protective layer may be wholly or partially transparent, semi-transparent, or opaque in the visible range to provide a desired appearance (e.g., a matte appearance). The protective layer may be colorless or may be wholly or partially colored.
[0098] The thickness of the protective layer can be, for example, about 1 micrometer or more, about 5 micrometers or more, about 10 micrometers or more, about 25 micrometers or more, or about 40 micrometers or more, and can be about 500 micrometers or less, about 300 micrometers or less, about 100 micrometers or less, about 50 micrometers or less, about 40 micrometers or less, or about 30 micrometers or less.
[0099] In some embodiments, the adhesive film of the present disclosure can have a decorative layer disposed on or under the substrate. The decorative layer can be applied to the entire surface or a portion of the substrate.
[0100] The decorative layer includes, but is not limited to, a color layer having a paint color, for example, a light color such as white or yellow, or a dark color such as red, brown, green, blue, gray, or black; a pattern layer that imparts a pattern, such as wood grain, stone grain, geometric pattern, or leather pattern, a logo, or a picture to an article; a relief layer having an uneven surface; and combinations thereof. The decorative layer of the present disclosure can also include a layer called a graphic image or a graphic layer.
[0101] Materials for the color layer are not limited to the following, but may include, for example, inorganic pigments such as carbon black, yellow lead, yellow iron oxide, red iron oxide, and red iron oxide; phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; organic pigments such as azo lake pigments, indigo pigments, perinone pigments, perylene pigments, quinophthalone pigments, dioxazine pigments, and quinacridone pigments such as quinacridone red, dispersed in a binder resin such as (meth)acrylic resin or polyurethane resin.
[0102] The color layer can be formed using such materials by a coating method such as gravure coating, roll coating, die coating, bar coating, or knife coating, or can be formed by a printing method such as inkjet printing, screen printing, gravure printing, offset printing, laser printing, or electrostatic printing.
[0103] The pattern layer is not limited to the following, but may be, for example, a pattern such as a design, logo, or picture applied to a substrate or the like using a printing method such as gravure printing, offset printing, inkjet printing, laser printing, screen printing, or electrostatic printing, or may be a film or sheet having a pattern, logo, or picture formed by coating such as gravure coating, roll coating, die coating, bar coating, or knife coating, punching, etching, or the like. As the material for the pattern layer, for example, the same material as that used for the color layer can be used.
[0104] The relief layer may be a thermoplastic resin film having a surface texture formed by a conventional method such as embossing, scratching, laser processing, dry etching, or hot pressing. The relief layer may also be formed by applying a thermosetting or ionizing radiation curable resin such as a curable (meth)acrylic resin onto a release liner having a texture, curing the resin by heating or exposure to ionizing radiation, and removing the release liner.
[0105] The thermoplastic resin, thermosetting resin, and ionizing radiation curable resin used in the relief layer are not particularly limited, and examples thereof include fluororesins, polyester resins such as PET and PEN, (meth)acrylic resins, polyolefin resins such as polyethylene and polypropylene, thermoplastic elastomers, polycarbonate resins, polyamide resins, ABS resins, acrylonitrile-styrene resins, polystyrene resins, vinyl chloride resins, polyurethane resins, etc. The relief layer may contain at least one of the pigments used in the color layer.
[0106] The thickness of the decorative layer may be appropriately adjusted depending on the required decorativeness, etc., and is not particularly limited, but can be, for example, about 1 micrometer or more, about 3 micrometers or more, or about 5 micrometers or more, and can be about 50 micrometers or less, about 40 micrometers or less, about 30 micrometers or less, about 20 micrometers or less, or about 15 micrometers or less.
[0107] The luster layer (sometimes referred to as a "metal layer") may be, but is not limited to, a layer containing a metal selected from aluminum, nickel, gold, silver, copper, platinum, chromium, iron, steel, tin, indium, titanium, lead, zinc, germanium, etc., or an alloy or compound thereof, formed on the entire surface or part of the substrate, protective layer, or decorative layer by vacuum deposition, sputtering, ion plating, plating, etc. The luster layer may be applied in the form of a foil or sheet.
[0108] There is no particular limit to the thickness of the luminous layer, and it can be appropriately selected according to the required performance (e.g., decorativeness, brightness, non-combustibility) and cost. For example, when non-combustibility is required in addition to decorativeness, the thickness of the luminous layer can be about 8 micrometers or more, about 10 micrometers or more, or about 15 micrometers or more, and can be about 200 micrometers or less, about 150 micrometers or less, or about 100 micrometers or less. For example, when the luminous layer contains aluminum, the thickness of the luminous layer can be about 12 micrometers or more, about 15 micrometers or more, or about 25 micrometers or more, and by making it about 30 micrometers or more, about 40 micrometers or more, or about 50 micrometers or more, more excellent non-combustibility can be obtained. When non-combustibility is not required, the thickness of the luminous layer can be less than about 8 micrometers or about 5 micrometers or less, and can be about 0.1 micrometers or more, about 0.5 micrometers or more, or about 1 micrometer or more.
[0109] In some embodiments, the adhesive film of the present disclosure may include a bonding layer for bonding each of the constituent layers. As the bonding layer, for example, a solvent-based, emulsion-based, pressure-sensitive, heat-sensitive, heat-curing, or UV-curing adhesive containing a known resin such as a (meth)acrylic resin, a polyolefin resin, a polyurethane resin, a polyester resin, a vinyl acetate resin, a silicone resin, or a rubber resin may be used. The bonding layer may be applied by a known coating method or the like.
[0110] The thickness of the bonding layer can be, for example, about 0.05 micrometers or more, about 0.5 micrometers or more, about 5 micrometers or more, about 10 micrometers or more, about 20 micrometers or more, or about 30 micrometers or more, and can be about 200 micrometers or less, about 100 micrometers or less, about 50 micrometers or less, about 20 micrometers or less, or about 10 micrometers or less.
[0111] In some embodiments, the additional layers such as the protective layer, decorative layer, and bonding layer may contain, as optional components, for example, fillers, reinforcing materials, antioxidants, flame retardants, antibacterial agents, deodorants, UV absorbers, light stabilizers, heat stabilizers, dispersants, plasticizers, flow improvers, tackifiers, leveling agents, silane coupling agents, catalysts, pigments, dyes, thickeners, binder resins, etc., depending on the intended use, etc. These optional components may be used alone or in combination of two or more.
[0112] The water-sealable decorative adhesive film of the present disclosure can be prepared by any of known methods, such as printing methods such as gravure direct printing, gravure offset printing, inkjet printing, and screen printing, coating methods such as gravure coating, roll coating, die coating, bar coating, knife coating, and extrusion coating, lamination methods, transfer methods, bonding methods, vapor deposition methods, and plating methods, either alone or in combination.
[0113] The following manufacturing method is described as an example, but the manufacturing method of the water-sealable decorative adhesive film of the present disclosure is not limited thereto. For example, in the case of a water-sealable decorative adhesive film having a configuration in which a release liner, an adhesive layer, a substrate, a bonding layer, a decorative layer, and a protective layer are sequentially provided, an adhesive composition containing a tacky binder, a crosslinking agent, and a water-absorbent resin is applied onto a release liner having an embossed pattern corresponding to the structured surface, and dried and / or crosslinked as necessary to prepare a laminate A containing an adhesive layer. After applying a composition for forming a bonding layer onto a substrate and drying and / or crosslinking as necessary to form a bonding layer, a resin film having a decorative layer on one side is laminated to the bonding layer via the decorative layer to prepare a laminate B. An adhesive film can be obtained by laminating the adhesive layer of the laminate A to the substrate surface of the laminate B. Crosslinking of the adhesive layer may be performed after laminating the laminate A and the laminate B.
[0114] Alternatively, an adhesive composition containing an adhesive binder, a crosslinking agent, microspheres, and a water-absorbing resin can be applied to the substrate surface of the above-mentioned laminate B, and then dried as necessary, followed by crosslinking to obtain an adhesive film.
[0115] The water sealable decorative adhesive film of the present disclosure can exhibit excellent water sealability and adhesion even though the adhesive layer has a structured surface.
[0116] The structured surface of the adhesive layer can be evaluated, for example, by the wet-out test described in the examples below. The smaller the wet-out rate determined by such a test, the smaller the contact area between the adherend and the adhesive layer, i.e., the greater the rate of channel formation, and the larger the wet-out rate, the larger the contact area between the adherend and the adhesive layer, i.e., the smaller the rate of channel formation. In some embodiments, the water-sealable decorative adhesive film of the present disclosure can achieve a wet-out rate of about 30% or more, about 35% or more, or about 40% or more, about 90% or less, about 88% or less, about 85% or less, or about 80% or less.
[0117] The water sealability can be evaluated, for example, by the water seal test described in the Examples below. In some embodiments, the water sealable decorative adhesive film of the present disclosure can be rated "B" or "A" in the water seal test.
[0118] The adhesiveness can be evaluated, for example, by the adhesive strength test described in the examples below. The adhesive strength of the adhesive film varies depending on the surface of the adherend, but in some embodiments, the water-sealable decorative adhesive film of the present disclosure can achieve a 180-degree peel strength of about 0.5 N / 25 mm or more, about 1 N / 25 mm or more, about 3 N / 25 mm or more, about 5 N / 25 mm or more, about 60 N / 25 mm or less, about 55 N / 25 mm or less, about 50 N / 25 mm or less, or about 45 N / 25 mm or less.
[0119] In addition, the shear force in the structure in which the adhesive film and the adherend are laminated varies depending on the surface of the adherend, but in some embodiments, the water-sealable decorative adhesive film of the present disclosure can achieve a shear force of about 0.05 MPa or more, or about 0.10 MPa or more, and about 1.5 MPa or less, or about 1.0 MPa or less. The adhesive film can exhibit high shear force, especially when applied to a rough surface. Without being bound by any theory, it is believed that this is due to the uneven surface of the adhesive layer engaging with the unevenness of the rough surface. High shear force is advantageous in preventing slippage of the adhesive sheet due to its own weight when the adhesive film is applied to a vertical surface. The shear strength is defined as the adhesive strength when a test piece is prepared by cutting the adhesive film into a rectangle of 25 mm width and 60 mm length, and the test piece is attached to an aluminum panel of 25 mm width, 60 mm length and 1 mm thickness with a roller at 23°C so that the contact area is 25 mm x 12 mm, and then left at 20°C for 24 hours and measured using a tensile tester at 20°C and a tensile speed of 50 mm / min.
[0120] According to one embodiment of the present disclosure, a structure is provided in which the adhesive layer of the above-mentioned water-sealing decorative adhesive film is disposed on the surface of an adherend. The adhesive film of the present disclosure can be applied not only to adherends having a substantially flat surface, but also to adherends having irregularities, or to adherends having a curved or three-dimensional shape, and can be used in a variety of applications.
[0121] The material of the adherend is not particularly limited, and for example, a resin material, an inorganic material (e.g., glass, ceramic, concrete), a metal material, a wood material, etc. can be used. The adhesive film of the present disclosure has a water sealing property, and is therefore useful when the adherend is applied to at least one member selected from a hydrophilic member, a hygroscopic member, and a porous member that easily attracts water to the interface between the adhesive layer and the adherend. Examples of materials of such members include glass, ceramic, concrete, and mortar. Here, "hydrophilic" can mean, for example, that the water contact angle of the outermost surface of the adherend is less than about 90°, about 70° or less, about 50° or less, or about 25° or less. This water contact angle can be a value measured in accordance with the sessile drop method described in JIS R 3257:1999. "Hygroscopicity" means the ability to absorb moisture from the surroundings, and the presence or absence of such ability can be confirmed, for example, by a moisture absorption and desorption test described in JIS A 1470-1:2014.
[0122] The water-sealable decorative adhesive film of the present disclosure can be applied to various applications and surfaces, and can be advantageously used in environments exposed to water. In some embodiments, the water-sealable decorative adhesive film of the present disclosure can be used for outdoor or indoor wet areas. Specifically, the water-sealable decorative adhesive film of the present disclosure can be used for walls, floors, ceilings, doors, windows, etc. of outdoor structures such as signs, billboards, and bridges, buildings such as houses and buildings, or indoors, such as kitchens, bathrooms, and toilets, which may be exposed to water. EXAMPLES
[0123] The following examples illustrate specific embodiments of the present disclosure, but the present invention is not limited thereto. All parts and percentages are by weight unless otherwise specified. In Table 1, "Tg" refers to glass transition temperature, and "Mw" refers to weight average molecular weight. Here, the glass transition temperature is a value calculated from the FOX formula assuming that the polymer is copolymerized from n types of monomers, and the weight average molecular weight is a weight average molecular weight in terms of polystyrene in tetrahydrofuran (THF) solvent measured by gel permeation chromatography.
[0124] The materials used in this example are shown in Table 1 below.
[0125] [Table 1]
[0126] (Preparation of Adhesive Binder 1 (ADH1)) 62 parts by mass of 2-ethylhexyl acrylate (2EHA), 32 parts by mass of butyl acrylate (BA), and 6 parts by mass of acrylic acid (AA) were dissolved in 66.7 parts by mass of ethyl acetate, and 0.7 parts by mass of dimethyl 2,2'-azobis(2-methylpropionate) (product name V-601, Fujifilm Wako Pure Chemical Industries, Ltd. (Osaka City, Osaka, Japan)) was added as a polymerization initiator, and the mixture was reacted at 75°C for 24 hours under a nitrogen atmosphere to prepare an ethyl acetate solution of adhesive binder 1 (ADH1) (solid content 60%). The weight average molecular weight (Mw) of ADH1 was 250,000 and the glass transition temperature (Tg) was -57°C.
[0127] (Preparation of Adhesive Binder 2 (ADH2)) 62 parts by mass of 2-ethylhexyl acrylate (2EHA), 32 parts by mass of butyl acrylate (BA), and 6 parts by mass of acrylic acid (AA) were dissolved in 66.7 parts by mass of ethyl acetate, and 0.55 parts by mass of dimethyl 2,2'-azobis(2-methylpropionate) (product name V-601, Fujifilm Wako Pure Chemical Industries, Ltd. (Osaka City, Osaka, Japan)) was added as a polymerization initiator, and the mixture was reacted at 75°C for 24 hours under a nitrogen atmosphere to prepare an ethyl acetate solution of adhesive binder 2 (ADH2) (solid content 60%). The weight average molecular weight (Mw) of ADH2 was 290,000 and the glass transition temperature (Tg) was -57°C.
[0128] Preparation of Elastic Resin Microspheres (LSA1) Elastic resin microspheres 1 (LSA1) were prepared as follows. 1.5 g of polyvinyl alcohol (saponification degree about 88 mol%, viscosity about 95 mPa·s, pH about 6) and 279 g of deionized water were added to a 1-liter baffled glass flask, and the mixture was heated to 45°C using an IR stirrer and mixed. After the polyvinyl alcohol particles were completely dissolved in water, a premix of 141 g of 2-ethylhexyl acrylate, 9 g of acrylic acid, and 0.0375 g of 1,4-butanediol diacrylate in a jar was poured into the flask, stirred at a stirring speed of 457 rpm using a 45 mm impeller blade, and the flask was heated again to 45°C while bubbling nitrogen gas into the mixture. At 45°C, 0.45 g of 2,2'-azobis(2,4-dimethylvaleronitrile) (AVN) was added to the mixture. Polymerization started about 1 hour after the addition of AVN, and the temperature rose due to an exothermic reaction. When the temperature stopped rising, the temperature setting was increased to 65°C and maintained at that temperature for 3 hours from the start of polymerization. After cooling, the resulting polymer suspension was filtered through a #16 metal mesh. The volume average particle size of the resulting microspheres was measured using a Beckman Coulter LS230 laser diffraction particle size analyzer. The volume average particle size of LSA1 was about 137 micrometers. The viscoelasticity of LSA1 was measured using a Rheometrics RSAII viscoelasticity spectrometer (Advanced Rheometric Expansion System (ARES)). The shear storage modulus at 25°C was 7×10 5 dyn / cm 2 The compressive elastic modulus is approximately 2.3 × 10 4 It was Pa.
[0129] (Resin (P1)) 60 parts by mass of methyl methacrylate (MMA), 34 parts by mass of butyl methacrylate (BMA), and 6 parts by mass of dimethylaminoethyl methacrylate (DMAEMA) were dissolved in 150 parts by mass of ethyl acetate, and 0.6 parts by mass of dimethyl-2,2-azobis(2-methylpropionate) (product name V-601, Fujifilm Wako Pure Chemical Industries, Ltd. (Osaka City, Osaka, Japan)) was added as a polymerization initiator, and the mixture was reacted at 65°C for 24 hours under a nitrogen atmosphere to prepare an ethyl acetate solution of high Tg resin (P1) (solid content 40%). The weight average molecular weight (Mw) of P1 was 68,000 and the glass transition temperature (Tg) was 63°C.
[0130] Example 1 ADH2, P1, PIG1 and CL1 were mixed to prepare a white bonding layer forming solution. The mass ratio of ADH2, PIG1, P1 and CL1 was 100:50:10:0.2 based on the non-volatile content (solid content). The non-volatile content (solid content) of the white bonding layer forming solution was about 55%. This white bonding layer forming solution was coated on PET1 with a knife coater. This coating layer was dried and crosslinked at about 95°C for about 5 minutes to obtain a white bonding layer with a thickness of about 30 micrometers. To temporarily protect the white bonding layer, a substantially flat release liner was laminated on this bonding layer.
[0131] An adhesive solution was prepared by mixing ADH1, LSA1, and SAP1. The mass ratio of ADH1, LSA1, and SAP1 was 100:25:2 based on the non-volatile content (solid content). The non-volatile content (solid content) of the adhesive solution was about 46%. CL1 was mixed into the adhesive solution. The mass ratio of ADH1 to CL1 was 100:0.20 based on the non-volatile content (solid content). The adhesive solution was coated with a knife coater on another surface of PET1 opposite to the white bonding layer. The coating was dried and crosslinked at about 95°C for about 5 minutes to obtain an adhesive layer about 104 micrometers thick with a structured surface. The dry coating weight of the adhesive layer containing the water-absorbing resin (SAP1) was about 70 g / m 2In order to temporarily protect the adhesive layer, a substantially flat release liner was laminated on the adhesive layer. After removing the release liner on the white bonding layer, Scotchcal (trademark) Paint Film PF997 (BSPC: a transparent film that can be printed on the reverse side, manufactured by 3M Japan Ltd.) having a graphic image was laminated to obtain the adhesive film of Example 1.
[0132] Example 2 The dry coating weight of the adhesive layer is approximately 75 g / m 2 An adhesive film of Example 2 was prepared in the same manner as in Example 1, except that the above-mentioned was changed to the above.
[0133] Example 3 PET1 with a white adhesive layer was prepared in the same manner as in Example 1. ADH3 and LSA1 were mixed to prepare a first adhesive solution. The mass ratio of ADH3 and LSA1 was 100:50 based on the non-volatile content (solid content). CL1 was mixed into the first adhesive solution. The mass ratio of ADH3 and CL1 was 100:0.09 based on the non-volatile content (solid content). The non-volatile content (solid content) of the first adhesive solution was about 46%. The first adhesive solution was coated on another surface of PET1 opposite to the white adhesive layer with a knife coater. The coating layer was dried and crosslinked at about 95°C for about 5 minutes to obtain a first adhesive layer with a thickness of about 70 micrometers and a structured surface. The dry coating weight of the first adhesive layer was about 53 g / m 2 It was.
[0134] A second adhesive solution was prepared by mixing ADH2, P1, SAP1, and CL1. The mass ratio of ADH2, P1, SAP1, and CL1 was 100:5:10:0.18 based on the non-volatile content (solid content). The non-volatile content (solid content) of the second adhesive solution was about 52%. The second adhesive solution was coated on the first adhesive layer with a knife coater. The coating was dried and crosslinked at about 95° C. for about 5 minutes to prepare a second adhesive layer containing a water-absorbing resin (SAP1) with a thickness of about 21 micrometers on the first adhesive layer having a structured surface. The dry coating weight of the second adhesive layer was about 41 g / m 2In order to temporarily protect the adhesive layer, a substantially flat release liner was laminated on the adhesive layer. After removing the release liner on the white bonding layer, Scotchcal (trademark) Paint Film PF997 (BSPC: a transparent film that can be printed on the back side, manufactured by 3M Japan Co., Ltd.) having a graphic image was laminated to obtain the adhesive film of Example 3.
[0135] Example 4 The dry coating weight of the second adhesive layer is about 42 g / m 2 An adhesive film of Example 4 was prepared in the same manner as in Example 3, except that the above-mentioned was changed to the above.
[0136] Example 5 The dry coating weight of the second adhesive layer is about 55 g / m 2 An adhesive film of Example 5 was prepared in the same manner as in Example 3, except that the above-mentioned was changed to the above.
[0137] Example 6 An adhesive solution was prepared by mixing ADH2, P1, SAP1 and CL1. The mass ratio of ADH2, P1, SAP1 and CL1 was 100:5:10:0.15 based on the non-volatile content (solid content). The non-volatile content (solid content) of the adhesive solution was about 52%. The adhesive solution was coated by a knife coater onto a release liner L1 having an embossed pattern corresponding to the structured surface. The coating layer was dried and crosslinked at about 95°C for about 5 minutes to prepare an adhesive layer having a structured surface containing a water-absorbing resin (SAP1) and having a thickness of about 41 micrometers. The dry coating weight of the adhesive layer was about 38 g / m 2 A polyvinyl chloride film having a thickness of about 50 micrometers was laminated on the adhesive layer containing this water-absorbent resin (SAP1) to obtain an adhesive film of Example 6.
[0138] Example 7 An adhesive film of Example 7 was prepared in the same manner as in Example 6, except that the mass ratio of the water-absorbing resin (SAP1) was changed to 5 parts by mass and the thickness of the adhesive layer was changed to about 39 micrometers.
[0139] Example 8 The adhesive film of Example 8 was prepared in the same manner as in Example 6, except that the polyvinyl chloride film was changed to a thickness of about 170 micrometers.
[0140] Example 9 The adhesive film of Example 9 was prepared in the same manner as in Example 7, except that the polyvinyl chloride film was changed to a thickness of about 170 micrometers.
[0141] Comparative Example 1 The adhesive film of Comparative Example 1 was prepared in the same manner as in Example 3, except that a second adhesive layer containing a water-absorbing resin (SAP1) was not provided on the first adhesive layer having a structured surface.
[0142] Comparative Example 2 An adhesive film of Comparative Example 2 was prepared in the same manner as in Example 6, except that the adhesive solution was changed to one that did not contain the water-absorbing resin (SAP1).
[0143] Comparative Example 3 An adhesive film of Comparative Example 3 was prepared in the same manner as in Example 8, except that the adhesive solution was changed to one not containing the water-absorbing resin (SAP1).
[0144] <Physical property evaluation test> The properties of the adhesive films were evaluated using the following methods.
[0145] (Water sealing test) The adhesive film was cut to a size of 25 mm wide and 60 mm long to prepare a test piece. This test piece was attached to a glass plate (manufactured by Matsunami Glass Industry Co., Ltd.) at 23°C. The end of the test piece was immersed in dyed water by about 5 mm to prepare a sample. The obtained sample was placed in a thermostatic chamber at 23°C. After 24 hours, the appearance of the adhesive surface was visually observed, and the water sealing property was evaluated according to the following criteria. Here, "A" and "B" correspond to pass, and "C" and "D" correspond to fail. Photographs of the samples of Comparative Example 1 and Examples 3 to 5 after the test are shown in Figure 5. In Figure 5, (a) corresponds to Comparative Example 1, (b) corresponds to Example 3, (c) corresponds to Example 4, and (d) corresponds to Example 5: A: The area penetrated by the dyeing water was 5% or less. B: The area penetrated by the dye water was more than 5% and less than 20%. C: The area penetrated by the dyeing water was more than 20%. D: The sample peeled off from the glass plate.
[0146] (Adhesion test) The adhesive film was cut to a size of 25 mm wide and 150 mm long to prepare test pieces. The test pieces were attached to a melamine-coated panel (manufactured by Partec Co., Ltd.), a mortar substrate, and a ceramic tile at 23°C. The attachment method was in accordance with JIS Z 0237 8.2.3. The test pieces were left at 20°C for 24 hours. The adhesive strength was measured using a tensile tester (Tensilon universal testing machine, model number: RTC-1210A, manufactured by A&D Co., Ltd.) at 20°C, a peeling speed of 300 mm / min, and a 180° peeling angle.
[0147] (Wet-out test) A glass slide (Matsunami Glass Industry Co., Ltd., MICRO SLIDE GLASS white edge polished No. 1, Ra of the flat surface is about 0.001 micrometers) with a length of 76 mm, width of 26 mm, and thickness of 1 mm was prepared. The adhesive layer surface of the adhesive film prepared to a size of 25 mm in width and 60 mm in length was attached to this glass slide, and pressed by three reciprocations in the length direction with a 2 kg roller to prepare a test piece. When white light was irradiated to the glass surface on which the adhesive film was not attached and observed through a polarizing filter, the area where the protruding adhesive part and the glass surface were in contact (contact area) appeared blackish, and the non-contact area appeared whitish. This procedure was performed using an optical microscope (EMP-ST, Kyowa Optical Co., Ltd.), and image data was captured into an image processing device (Excell-II, Nippon Avionics Co., Ltd.) via a CCD camera (TI-32XA, NEC Corporation). The ratio of the total contact area to the total area of the observation field (corresponding to the apparent contact area) was expressed as a percentage and was taken as the "wet-out rate." The area of the observation field was approximately 1 cm 2 It was.
[0148] Details of the adhesive layer of the prepared adhesive film are shown in Table 2, and the evaluation results are shown in Table 3. Here, the adhesive binder in Examples 3 to 5 in Table 2 refers to the adhesive binder used in the second adhesive layer. Items not evaluated in Table 3 are indicated as ND.
[0149] [Table 2]
[0150] [Table 3]
[0151] It will be apparent to those skilled in the art that the above-described embodiments and examples can be modified in various ways without departing from the basic principles of the present invention, and that various improvements and modifications of the present invention can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0152] 100, 200, 300, 400 Water-sealable decorative adhesive film 101, 201, 301, 401 Base material 105, 205, 305, 405 Adhesive layer 202 First adhesive layer 203 Second adhesive layer 107, 207 microspheres 309 Release liner having embossed pattern corresponding to structured surface 410 Adherent Some of the embodiments of the present disclosure are described in [Item 1] to [Item 11] below. [Item 1] A substrate, and an adhesive layer having a structured surface disposed on the substrate, the adhesive layer comprising a tacky binder having a crosslinked structure derived from a crosslinking agent, and a water-absorbing resin; Equipped with Water-sealable decorative adhesive film. [Item 2] 2. The adhesive film according to item 1, wherein the adhesive binder comprises a (meth)acrylic resin. [Item 3] 3. The adhesive film according to item 1 or 2, wherein the content of the water-absorbing resin is 1 part by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the adhesive binder. [Item 4] 4. The adhesive film according to any one of items 1 to 3, wherein a release liner having a textured surface corresponding to the structured surface is disposed on the adhesive layer via the textured surface. [Item 5] 4. The adhesive film according to any one of items 1 to 3, wherein the adhesive layer contains microspheres having a volume average particle diameter of 110 micrometers or more. [Item 6] 4. The adhesive film according to any one of items 1 to 3, wherein the adhesive layer comprises a first adhesive layer located on the substrate side and a second adhesive layer located on the outermost surface, the first adhesive layer contains an adhesive binder having a crosslinked structure derived from a crosslinking agent, and microspheres having a volume average particle diameter of 110 micrometers or more, and the second adhesive layer contains an adhesive binder having a crosslinked structure derived from a crosslinking agent, and a water-absorbent resin. [Item 7] 7. The adhesive film according to claim 5 or 6, wherein the microspheres comprise a (meth)acrylic resin. [Item 8] 8. The adhesive film according to any one of items 1 to 7, which is used outdoors. [Item 9] 8. The adhesive film according to any one of items 1 to 7, which is used for indoor wet areas. [Item 10] 10. A structure, comprising the adhesive film according to any one of items 1 to 9, disposed on an adherend via the adhesive layer. [Item 11] Item 11. The structure according to item 10, wherein the adherend is at least one member selected from the group consisting of a hydrophilic material, a hygroscopic material, and a porous material.
Claims
1. A substrate, and an adhesive layer having a structured surface disposed on the substrate, the adhesive layer comprising a tacky binder having a crosslinked structure derived from a crosslinking agent, and a water-absorbing resin; Equipped with The structured surface forms channels that communicate with the outside air at the interface between the adhesive layer and the adherend when the adhesive layer is applied to the adherend, in a water-sealable decorative adhesive film.
2. The adhesive film of claim 1 , wherein the adhesive binder comprises a (meth)acrylic resin.
3. The adhesive film according to claim 1 or 2, wherein the content of the water-absorbing resin is 1 part by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the adhesive binder.
4. The adhesive film according to any one of claims 1 to 3, wherein a release liner having an uneven surface corresponding to the structured surface is disposed on the adhesive layer via the uneven surface.
5. The adhesive film according to any one of claims 1 to 3, wherein the adhesive layer contains microspheres having a volume average particle size of 110 micrometers or more.
6. The adhesive film according to any one of claims 1 to 3, wherein the adhesive layer comprises a first adhesive layer located on the substrate side and a second adhesive layer located on the outermost surface, the first adhesive layer contains an adhesive binder having a crosslinked structure derived from a crosslinking agent, and microspheres having a volume average particle diameter of 110 micrometers or more, and the second adhesive layer contains an adhesive binder having a crosslinked structure derived from a crosslinking agent, and a water-absorbent resin.
7. The adhesive film according to claim 5 or 6, wherein the microspheres comprise a (meth)acrylic resin.
8. The adhesive film according to any one of claims 1 to 7, which is used outdoors.
9. The adhesive film according to any one of claims 1 to 7, which is used for indoor wet areas.
10. A structure comprising the adhesive film according to any one of claims 1 to 9, disposed on an adherend via the adhesive layer.
11. The structure according to claim 10 , wherein the adherend is at least one member selected from the group consisting of a hydrophilic material, a hygroscopic material, and a porous material.
Citation Information
Patent Citations
Water stopping material and water stopping
JP1988304082A
Pressure-sensitive adhesive sheet, its production and pressure-sensitive adhesive sheet stick structure
JP1997157606A
Waterproofing tape
JP2002201460A
Adhesive sheet and method of applying adhesive sheet to rough surface
JP2018178080A
Adhesive sheet and method of applying adhesive sheet to rough surface
JP2020100721A